Formulae for anti-triangular block matrices which include the Drazin inverse - Zhang, Daochang; Mosic, Dijana; Stanimirovic, Predrag (Applicable analysis and discrete mathematics, 2025)
The expressions for the Drazin inverse of two kinds of anti-triangular block matrices are developed under new and weaker assumptions relative to those already used recently in this subject. Applying our results concerning the Drazin inverse and anti-triangular block matrices, we propose some characterizations and representations of the Drazin inverse of a 2?2 block matrix. In this way, we expand some notable achievements in characterizing and representing generalized inverses of partitioned matrices.